(3OhQ GdeDSSGJ GdEbJUGOjI aj YedjGJ GdJfejI GdeSJOGeI (B/s - (3LQjh, eMeO GdCejfs ((3GdLRGFQ(B: s (3GdfTQ GdLGeYj GdLOjO(B, s, 2020)
(3JfGhd GdcGJH OhQ GdeDSSGJ GdGbJUGOjI aj YedjGJ GdJfejI GdeSJOGeI, MjK JMOK ef NdGd aUhd OQGSJg Yf QgGfGJ GdeDSSI hGdJfejI GdeSJOGeI hjTed GdeDSSI GdGbJUGOjI hJMOjGJ GdJfejI GdHjFjI hGdGLJeGYjI, h ETcGdjI GdJfejI GdeSJOGeI dOi GdeDSSGJ GdGbJUGOjI(B. (3ceG JMOK cPdc Yf COhGJ JMbjb GdeDSSI GdGbJUGOjI dCOhGQgG aj GdJfejI GdeSJOGeI, hGdeSDhdjI GdHjFjI hGdGLJeGYjI ddeDSSI GdGbJUGOjI cVQhQI jaQVgG GdhGbY, hGYJeGO GdebGjjS GdOhdjI cNjGQ ddJfejI GdeSJOGeI ddeDSSI GdGbJUGOjI(B. s
Keywords: (3GdJfejI GdGbJUGOjIs; (3GdJfejI GdeSJOGeIs; (3GdeDSSGJ GdGbJUGOjIs